Chloroma of the testis in a patient with a history of acute myeloid leukemia - Mohammad Hossein Sanei (Journal of Research in Medical Sciences, 2017)
Chloroma, or granulocytic sarcoma, is a rare extramedullary solid hematologic cancer, found concomitant with acute myeloid leukemia. It is infrequently associated with other myeloproliferative disorders or chronic myelogenous leukemia. Chloroma of the testis after allogeneic bone marrow transplantation is particularly sparsely represented in the literature. It is suggested that an appropriate panel of marker studies be performed along with clinical correlation and circumspection to avoid misleading conclusions. We report an interesting case of a 32-year-old male with a clinical history of acute myelogenous leukemia, postallogeneic peripheral blood stem cell transplantation that was found to have chloroma of the right testis.